EVALUASI PEMBELAJARAN BIOLOGI DI SMAN 10 KOTA BENGKULU MENGGUNAKAN MODEL COUNTENANCE STAKE - Alwina Sucita; Dinda Lestari; Fopy Angraini; Siska Selpiyanti; Ahmad Walid (Jurnal Muara Pendidikan, 2020)
Evaluation of Biology Learning at SMAN 10 Bengkulu City Using the Countenance Stake Model. In the world of education, learning evaluation is a process to determine the value of learning and learning implemented, through assessment and / or measurement of learning and learning activities. This study aims to evaluate the Biology learning at SMAN 10 Bengkulu City based on the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 65 of 2013 concerning Basic and Secondary Education Process Standards. This research is an evaluation research using the Countenace Stake model. Data collection using techniques, observation, interviews and documentation. The analysis technique used is descriptive qualitative. The conclusions of the results of the study are as follows: (1) Biology learning planning is included in the sufficient category (70%), it is found that there is no conformity between the lesson plan and the standard of the learning process; (2) the implementation of Biology learning is included in the sufficient category (58%), there is no conformity between the implementation of learning with the standard implementation of learning processes; and (3) student learning outcomes have not met the Minimum Mastery Criteria (KKM) with an actuality of achievement of 65% sufficient category. 4) there is a contingency between planning, implementation and learning outcomes of science, which planning learning with enough categories causes the teacher to carry out learning not in accordance with the standard processes so that the learning outcomes of students do not meet the KKM.